Educational practices for the language development of students with intellectual developmental disorder in the school setting: a systematic review - Janho dit Hreich, Céline; Ibernon, Laure; Bourdin, Béatrice (Frontiers in Education, 2024)
Background: Intellectual development disorder (IDD) is a challenging disorder that professionals, most notably teachers, are confronted with daily. Supporting oral language in the classroom is a complex challenge as teachers are expected to implement effective methods to support students' language. However, they face a persistent scarcity of scientific evidence to draw upon in their practice. Aims:This research provides a first overview of instructional methods and their effectiveness in this population. Method: Our search was conducted through various databases, generating a total of 931 articles. Data from the 14 selected studies were analyzed. Outcomes & Results: The results reveal limited, heterogenous, and hardly comparable studies in terms of their characteristics (samples, language area, strategies, and effectiveness measures) suggesting a low level of evidence regarding the effectiveness of these practices. Conclusion & Implications: We discuss the implications of these findings in light of the different factors contributing to the interventions' effectiveness, as well as considering the issue of transfer and generalization of acquired skills in IDD. We also reveal the urgent need for developing methods addressing cognitive load limitations such as implicit learning approaches, to enhances effectiveness and compensate the gap of available resources tailored to improve oral language outcomes in the IDD population.